Parenting styles as predictors of disposition to antisocial behaviour among adolescents in Sanyati district - Gwanyanya, Lovemore (Midlands State University, 2017)
This study investigated the influence of permissive, authoritarian and authoritative parenting styles as predictors of disposition towards antisocial behaviour among adolescents. One hundred and thirteen (113) students from Neuso High and ST Charles Secondary Schools in Sanyati District participated in the study. Participants were drawn from Form 1 to Form 4, both boys and girls. Data was entered using the Statistical Package for Social Sciences (SPSS) and analysed using both descriptive and inferential statistics. The Pearson’s Product Moment Correlation was computed to establish the relationship between parenting styles and anti-social behaviour. The results showed nonsignificant main effects of parenting styles on antisocial behaviour between participants from permissive (r =.031 p, <.747), authoritarian (r =.048, p<.615) and authoritative (r =.199, p<.034). The results were discussed in terms of their implications in antisocial behaviour and suggestions were made for further studies.